Implementasi dan Tantangan Revitalisasi Bahasa Daerah di Provinsi Lampung - Andina, Elga (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2023)
The revitalization of local languages in Indonesia has become an increasingly important issue and required serious attention. The Ministry Of Education, Culture, Research and Technology responded to this crisis by implementing Merdeka Belajar Episode 17, which focuses on revitalizing local languages in the province of Lampung in 2023. This research aims to evaluate the challenges of revitalizing local languages implemented by the government in Lampung province. Using a qualitative descriptive approach with a case study pattern, primary data was obtained from interviews and focused group discussions with government agencies involved in revitalizing local languages, including the Lampung Provincial Language Office, the Lampung Provincial Education Office, and the Welfare Department of the Lampung Provincial Government, in addition to academic from Lampung University. The study found that in Lampung province, revitalization is carried out through structured learning activities in schools by using the Model B approach, which included teaching local content, especially Lampung language. Although there are compulsory regulations to teach Lampung language in primary and secondary schools, several challenges have still remained, such as psychological barriers faced by communities in using local languages, insufficient support from the government, and weak interagency coordination in implementing language revitalization programs. Overcoming these challenges requires joint efforts from all parties to promote the use of local languages and document them, provide consistent government support, and increase public awareness of the importance of preserving them. It is expected that the result of this study can contribute to the improvement and enrichment of the cultural diversity in Indonesia.AbstrakRevitalisasi bahasa daerah di Indonesia telah menjadi isu yang semakin penting dan memerlukan perhatian serius. Kemendikbudristek merespons krisis tersebut dengan menerapkan Merdeka Belajar Episode 17 Revitalisasi Bahasa Daerah di Provinsi Lampung pada tahun 2023. Penelitian ini bertujuan untuk mengevaluasi tantangan implementasi revitalisasi bahasa daerah yang dilaksanakan pemerintah di Provinsi Lampung. Dengan menggunakan pendekatan deskriptif kualitatif dengan pola studi kasus, data primer diperoleh dari wawancara dan diskusi kelompok terfokus dengan instansi pemerintah pelaksana revitalisasi bahasa daerah, yaitu Kantor Bahasa Provinsi Lampung, Dinas Pendidikan Provinsi Lampung, dan Bidang Kesra Pemerintah Provinsi Lampung, ditambah dengan akademisi Universitas Lampung. Penelitian ini menemukan bahwa di Provinsi Lampung revitalisasi dilakukan melalui kegiatan pembelajaran terstruktur di sekolah dengan menggunakan pendekatan Model B yang mencakup pengajaran konten lokal, khususnya bahasa Lampung. Meskipun sudah ada regulasi untuk mengajarkan bahasa Lampung di sekolah dasar dan menengah, tantangan masih ada seperti hambatan psikologis yang dihadapi oleh masyarakat dalam menggunakan bahasa daerah, dukungan yang kurang dari pemerintah, dan koordinasi antarlembaga yang lemah dalam menjalankan program pemulihan bahasa daerah. Untuk mengatasi tantangan tersebut, dibutuhkan upaya bersama dari semua pihak untuk mempromosikan penggunaan bahasa daerah, mendokumentasikannya, memberikan dukungan pemerintah yang konsisten, dan meningkatkan kesadaran publik akan pentingnya melestarikannya. Dengan melakukan hal tersebut, bahasa daerah di Indonesia dapat terus berkembang dan memperkaya keanekaragaman budaya di negara ini.